DEVELOPMENT OF QUIZ LEARNING MEDIA USING CHAT FORMS APPLICATIONS IN ISLAMIC RELIGIOUS EDUCATION AND ETHICS SUBJECTS - Agam Gunawan; Sholeh Hidayat; Cucu Atikah (Pusat Penerbitan Universitas (P2U) Unisba, 2022)
This study aims to develop learning media, analyze feasibility, analyze effectiveness, and analyze student responses to quiz learning media on Islamic religious education and ethics subjects, the pleasure of having commendable morals using the Chat Forms application for grade VI students of Batok Bali Elementary School, Serang City. The method used is R and D (Research and Development), and the development model used is the Borg and Gall model. The results of trials by media experts, learning material experts, and users (students) using closed questionnaires, respectively, the numbers obtained are 91.1%, 88.4%, and 87.5% and get the post-test scores of students with an average of 91.11. If it is included in the test results criteria table, it can be said that the Chat Forms application product that has been developed is valid and suitable for use in learning, especially in Islamic religious education and ethics subjects in class VI Batok Bali Elementary School, Serang City and can increase the effectiveness of learning.